Equine strangles: An update on disease control and prevention - Duran, María C.; Goehring, Lutz S. (Austral Journal of Veterinary Sciences, 2021)
Streptococcus equi spp. equi (SEE) causes a disease in horses commonly referred to as strangles. Carrier or reservoir equids are important for the maintenance of the bacteria between epizootics and the initiation of outbreaks on premises, they also make the control and prevention of the disease more difficult. Disease outbreaks are common in many countries, affecting negatively equine health and causing major economic losses to the equine industry. This review describes general aspects of the disease caused by SEE in horses (clinical signs, pathogenesis, epidemiology, treatment, complications) and then focuses on prevention, control and eradication mechanisms.